Design and applications of MEMS flow sensors: A review - Ejeian, Fatemeh; Azadi, Shohreh; Razmjou, Amir; Orooji, Yasin; Kottapalli, Ajay; Ebrahimi Warkiani, Majid; Asadnia, Mohsen (Sensors and actuators. A. Physical., 2019)
[Display omitted] There is an indispensable need for fluid flow rate and direction sensors in various medical, industrial and environmental applications. Besides the critical demands on sensing range of flow parameters (such as rate, velocity, direction and temperature), the properties of different target gases or liquids to be sensed pose challenges to the development of reliable, inexpensive and low powered sensors. This paper presents an overview of the work done on design and development of Microelectromechanical system (MEMS)-based flow sensors in recent years. In spite of using some similar principles, diverse production methods, analysis strategies, and different sensing materials, MEMS flow sensors can be broadly categorized into three main types, namely thermal sensors, piezoresistive sensors and piezoelectric sensors. Additionally, some key challenges and future prospects for the use of the MEMS flow sensors are discussed briefly.